TP10.1.13A model for safe elective liver resection during the SARS-CoV-2 (COVID-19) pandemic – lessons for enhanced recovery. (28th October 2021) - Jitsumura, Maki; Sethi, Pulkit; Welsh, Fenella KS; Chandrakumaran, Kandiah; Rees, Myrddin
Abstract: Background: The COVID-19 outbreak in January 2020 rapidly became a pandemic, adversely impacting elective cancer services in the UK. This study describes the pandemic-driven changes to existing admission and enhanced recovery protocols, which allowed the Unit to maintain a liver resection service, and evaluates their impact on patient safety. Methods: During the pandemic, all patients undergoing liver resection in this Unit isolated for 14 days prior to their admission, with COVID-19 testing 48 hours pre-admission. Patients were admitted on the day of surgery to the day surgery unit, a designated COVID-free environment. They underwent liver surgery, recovery and post-operative care, all within the day surgery unit. Using a prospectively collected database, short-term outcomes of consecutive patients undergoing elective hepatectomy during the COVID-19 pandemic (April - June 2020) were retrospectively compared to patients during the same period in 2019. Results: During the pandemic, 24 patients underwent hepatectomy compared to 34 patients in 2019. There was no statistical difference in demographics, indications for surgery, intra-operative parameters or complications between these periods. The median post-operative length of stay (LOS) was significantly shorter during the pandemic [3 (IQR: 3-4) days vs. 4 (IQR; 4-7) days, p = 0.015], as was the overall LOS [4 (IQR: 4-6) days vs. 6 (IQR; 5-9) days, p = 0.006]. No patient contracted COVID-19 per-operatively. Conclusions: Patient pathway changes during a pandemic enabled safe liver surgery to be undertaken with improved outcomes – a model that is transferrable to other Units.